The other Alcott [compact disc, unabridged] - Hooper, Elise (Harper Collins Publishers, 2017)
Stylish, outgoing, creative, May Alcott grows up longing to experience the wide world beyond Concord, Massachusetts. While her sister Louisa crafts stories, May herself is a talented and dedicated artist, taking lessons in Boston, turning down a marriage proposal from a well-off suitor, and facing scorn for entering what is very much a man's profession. Life for the Alcott family has never been easy, so when Louisa's Little Women is published, its success eases the financial burdens they'd faced for so many years. Everyone agrees the novel is charming, but May is struck to the core by the portrayal of selfish, spoiled 'Amy March'. Is this what her beloved sister really thinks of her? So May embarks on a quest to discover her own true identity, as an artist and a woman. From Boston to Rome, London, and Paris, this brave, talented, and determined woman forges an amazing life of her own.